2022
DOI: 10.1021/acs.jafc.2c06630
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Monoamine Oxidase B Inhibitors from Fragaria nubicola by Ligand Fishing and Their Neuroprotective Effects

Abstract: Fragaria nubicola, known as Tibetan strawberry, is an edible plant possessing various health-promoting effects. However, its functional compositions were rarely studied. In this work, monoamine oxidase B (MAO-B) inhibitors in this plant were rapidly screened using the enzyme-functionalized magnetic nanoparticles coupled with UPLC-QTOF-MS. Two inhibitors, quercetin-3-O-β-D-glucuronide-6″-methyl ester (1) and kaempferol-3-O-β-D-glucuronide-6″-methyl ester (2), were identified from this plant with the IC 50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…The S0 showed several peaks, while the S5 showed only two corresponding major ligands in the chromatogram ( Figure 2 ). Similar procedures and protocols have been successfully utilized on several MNP ligand fishing techniques, thus confirming the reliability of the magnetic nanoparticle solid phase extraction [ 41 , 42 ]. Furthermore, using MNPs@COOH as the blank control showed that no compound was observed in the corresponding HPLC-UV, confirming a non-specific binding on MNPs@MAO-B.…”
Section: Resultsmentioning
confidence: 73%
“…The S0 showed several peaks, while the S5 showed only two corresponding major ligands in the chromatogram ( Figure 2 ). Similar procedures and protocols have been successfully utilized on several MNP ligand fishing techniques, thus confirming the reliability of the magnetic nanoparticle solid phase extraction [ 41 , 42 ]. Furthermore, using MNPs@COOH as the blank control showed that no compound was observed in the corresponding HPLC-UV, confirming a non-specific binding on MNPs@MAO-B.…”
Section: Resultsmentioning
confidence: 73%
“…Screening for MAO-B inhibitors from natural products mainly relies on bioassay-guided separation, which often suffers from frequent fractionation and long run times, high costs, and the loss of active substances 10 . To overcome these limitations, magnetic bead ligand fishing 11 and affinity ultrafiltration methods 12 have been proposed, enabling rapid separation of active compound groups and shortening the screening period to several months 13 , 14 , 15 . However, these methods also have limitations, including low throughput and the need for separate analysis after the identification of the active components.…”
Section: Introductionmentioning
confidence: 99%